2012
DOI: 10.1590/s0103-05822012000300003
|View full text |Cite
|
Sign up to set email alerts
|

O uso das curvas de crescimento da Organização Mundial da Saúde em crianças e adolescentes que vivem em regiões de altitude moderada

Abstract: OBJETIVO: Determinar a aplicabilidade do uso das curvas de crescimento da Organização Mundial da Saúde (OMS) em escolares que vivem em regiões de altitude moderada. MÉTODOS: Estudo transversal cuja população foi constituída por uma amostra probabilística estratificada com 955 crianças e adolescentes de seis a 12 anos, sendo 473 meninos e 482 meninas que frequentavam escolas públicas da área urbana da Região de Arequipa (Peru). As variáveis avaliadas envolveram medidas de massa corpórea (kg) e estatura (m) e ín… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…When compared by gender, the taller the boy, the larger the BMI. This is also the case in girls, although this correlation is stronger for males, converging with the results of the studies 19,20 , performed this comparison between genders, identifying that the BMI value is equivalent to the height of each child, without differences between genders, convergent with the outcome of this study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…When compared by gender, the taller the boy, the larger the BMI. This is also the case in girls, although this correlation is stronger for males, converging with the results of the studies 19,20 , performed this comparison between genders, identifying that the BMI value is equivalent to the height of each child, without differences between genders, convergent with the outcome of this study.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have shown that height is a risk factor and that BMI, associated with the height, can be a good anthropometric indicator for the health of children and adolescents. It is also important to consider if there are regular changes in body composition during the process of development, tending to change the points of the cut for some of the anthropometric measures 9,19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation